Profile, Trends, and Determinants of Pregnancy Termination Among Filipino Women - Tena, Mejedin (Social Sciences and Development Review, 2025)
Cultural and legal barriers force many Filipino women to undergo unsafe and secret abortions. This study examines the profile of women who terminated pregnancy among those who gave birth in the last five years according to selected independent variables, and the trends in pregnancy termination from 1992 to 2022 all National Demographic and Health Surveys.  It also identified the determinants of pregnancy termination and estimated its likelihood. The analysis accounted for the complex survey design. Descriptive statistics, bivariate analysis, and multivariate logistic regression were employed. Results show that nearly 13% of women who gave birth in the last five years experienced pregnancy termination, and the distribution varies according to selected independent variables. Termination rates remained from 1997 to 2007 but declined in 2022. Logistic regression identified age as the strongest predictor, with odds rising sharply over time. Belonging to wealthier quintiles and having good self-rated health reduced the likelihood of termination, while education, marital status, religion, and residence showed no independent significance. Older, low-income, and poor health remain at higher risk, highlighting the need for targeted support. Expanding access to family planning, improving maternal healthcare, and addressing economic vulnerabilities can help reduce unintended pregnancies and unsafe abortions. Strengthening reproductive rights policies and ensuring access to safe abortion-related care and the legalization of abortion in the country are also crucial steps in promoting women’s health and well-being.
Keywords: Abortion; Determinants; Pregnancy Termination; Five years; Reproductive Aged